Maintenance Design of The Main Engine Support Systems on KMP. Kormomolin Under System Dynamics Scheme - Klara, Syerly; Hariyanto, Surya; Mahmuddin, Faisal; Shantya, Puput (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2023)
The operational activities of the ship's main engine support system elevated the possibility of failure. The main engine support system at KMP. Cormomolin, which belongs to PT. ASDP Indonesia Ferry (Persero), is extremely crucial to the ship's operation. Once the ship is not sailing, maintenance and repair can be handled. The component evaluation engine can be employed to accurately estimate inadequacies in the main support system. Failure Mode Effect and Critical Analysis (FMECA) identifies the root cause of critical component failures such as filters in the fuel system and cooler and sea chest filters in the cooling system. This study generates maintenance recommendations for the main engine support system for five years, including: fuel oil filter maintenance intervals every 151 hours at a cost of IDR 14,169,072, cooler maintenance intervals every 2481 hours at a cost of IDR 16,313,508, and sea chest filter maintenance intervals every 722 hours at a cost of IDR 11,167,152. For the fuel system, the cost care percentage is 81%, and for the cooling system, it is 46% after 5 years.